Acute Toxicity Study of Parangipattai Rasayanam PRM in Mice A Safety Assessment WHO guidelines 1993 - Vithyapathi Velmurugan, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Acute Toxicity Study of Parangipattai Rasayanam PRM in Mice A Safety Assessment WHO guidelines 1993